1-methyl-2, 4, 5-trinitroimidazole (MTNI), a melt-cast explosive: synthesis and studies on thermal behavior in presence of explosive ingredients. Issue 1 (2nd January 2020) - Anniyappan, M.; Vijay Varma, K.; Amit, R.S.; Nair, J.K
ABSTRACT: Traditionally, TNT based melt-castable explosives have been used till date. Recently, energetics communities are looking for an alternate to TNT in melt-cast formulation because of its toxicity and environmental concerns. 1-Methyl-2, 4, 5-trinitroimidazole (MTNI) is an insensitive high energy material and potential for use as a melt-cast high explosive formulations in place of TNT. MTNI has superior explosive performance as compared to that of TNT. Typically MTNI is synthesized starting from imidazole by step-wise nitration using strong nitric acid mixture followed by N-methylation offers poor yield. The key step involves during synthesis of MTNI is substitution of third nitro group at fifth position of 2, 4-dinitroimidaziole which is limiting for its large-scale preparation. We report herein, an improved method for synthesis of MTNI from 1-methyl-2, 4-Dinitroimidazole (MDNI) under different nitration conditions in good yield. Heteropoly acid (HPA) is an efficient, mild and green catalysts used as nitric acid activator. The synthesized MTNI by this method was characterized by FT-IR, NMR & elemental analysis. Thermal behavior of MTNI was determined by differential scanning calorimeter (DSC), thermogravimetric analysis (TGA) and ignition temperature tester. Further, the effects of thermal energy on decomposition of formulations containing MTNI with solid high explosives such as RDX & CL-20 or polymeric binders like HTPB & GAP were investigated. Thermal decomposition mechanisms of MTNI and its precursor, MDNI based on Pyrolysis-GC/MS analysis were also described.